Divided we fall: Congressional cycles, the stock market and firm performance - Livnat, Joshua; Rubin, Amir; Segal, Dan (Journal of Corporate Finance, 2025)
This study examines the impact of partisan control of the United States Congress on corporations and the economy. The findings indicate that economic performance is weaker when neither party holds a majority in both chambers of Congress, resulting in a divided Congress. We propose that this outcome may be attributed to a decrease in the level and quality of regulation during divided Congress terms. To analyze the immediate effects of regulation on the economy, we leverage congressional recess periods as a source of exogenous variation. Consistent with the conjecture that the composition of Congress affects the economy through its regulatory activity, we demonstrate that a divided Congress negatively impacts economic performance when Congress is in session but has no significant effect during recesses (when regulation does not occur). In conclusion, congressional cycles and the presence of effective regulation are shown to be crucial factors influencing economic activity.